2008
DOI: 10.1002/jid.1473
|View full text |Cite
|
Sign up to set email alerts
|

Pacific islands' bilateral trade: the role of remoteness and of transport costs

Abstract: Bilateral trade of geographically distant countries is likely to be negatively affected by the distance separating them from their trading partners and positively affected by their remoteness, defined as the average weighted distance between two countries with weights reflecting the absorptive capacity of the partner country. In presence of competitive transport costs, the effect of remoteness and distance is diluted. An augmented gravity model applied to the Pacific islands' bilateral trade from 1980 to 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
14
0
3
Order By: Relevance
“…This has been verified for the Pacific Islands (Borgatti 2008;McGillivray et al 2008); for Africa (Musila 2004(Musila , 2005 and for the Caribbean (Sandberg et al 2006). In all cases, distance elevated transportation costs and impaired global trade involvement.…”
Section: Distance From Major Marketsmentioning
confidence: 96%
“…This has been verified for the Pacific Islands (Borgatti 2008;McGillivray et al 2008); for Africa (Musila 2004(Musila , 2005 and for the Caribbean (Sandberg et al 2006). In all cases, distance elevated transportation costs and impaired global trade involvement.…”
Section: Distance From Major Marketsmentioning
confidence: 96%
“…Remoteness can be defined as the average weighted distance between two countries with weights reflecting the absorptive capacity of the partner country (Borgatti , 2007). According to this definition, two countries which are remote will tend to have a higher bilateral trade, having less commercial relationship with the rest of the world so that the negative effect of being remote could be partially offset by an increased trade with a "partner" country 11 .…”
Section: Remotenessmentioning
confidence: 99%
“…Borgatti (2007) using an augmented gravity model, analyze the Pacific islands' bilateral trade between 1980 and 2004. She eventually found that trade is negatively affected by distance, since the positive effect of remoteness is not big enough to compensate for distance.12 AsBriguglio (1995) point out, the role of remoteness in the definition of islands needs to be tackled with care, since not all islands are situated in remote areas.…”
mentioning
confidence: 99%
“…Briguglio, 1995;Armstrong and Read, 2003;Winters and Martins, 2004;Feeny and Rogers, 2008;Read, 2008). These accounts-largely economic-driven and policy-driven pieces on development, smallness and vulnerability that make up the lion's share of the literature-make a number of assumptions about size, resource endowment, isolation, productive capacity, vulnerability to environmental and natural disasters, and diversification (see World Bank, 1994;Commonwealth Secretariat, 1997;Winters, 2005Winters, , 2006Winters and Martins, 2005;Borgatti, 2008;McGillivray et al, 2008) that are then used to generate data sets and determine various indexes into which small island states are inserted and compared.…”
Section: Small Island State Development: Existing Wisdommentioning
confidence: 99%